IMPLEMENTASI MODEL PEMBELAJARAN RESOURCE BASED LEARNING (RBL) UNTUK MENIGKATKAN AKTIFITAS PEMBELAJARAN MATEMATIKA SISWA KELAS 6 SDN 02 DOMPU - Mujiono Sang Putra; Muhammad Wahyu Setiyadi; Kamaluddin Kamaluddin; Edi Firmansyah (STKIP Bina Bangsa Meulaboh, 2023)
AbstractThis study aims to determine: 1) the application of the Resource Based Learning learning model in mathematics that utilizes school environments as learning resources at MTs.Al.Amin Malang; 2) mathematics learning activities with the Resource Based Learning model; 3) student responses after learning mathematics with a Resource Based Learnig model.This research uses a qualitative approach with a descriptive type of research. The data taken are the results of observations of student activities, the results of student responses, with a Resource Based Learnig learning model, while the source of data in this study is 32 students in the SD N 2 Dompu class and those who become teachers are researchers themselves. The results showed that after applying mathematics learning using the Resource Based Learnig learning model in accordance with the steps that had been made before. From the results of observations of student activities, an average of 64.82% with a fairly good category, and the response of students to learning 78.12% with a good category. Keywords: Implementation, Resource Based Learning, Mathematics